2015
DOI: 10.1111/php.12537
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Modification in Human Hair: The Effect of the Levels of Cu (II) Ions, UV Exposure and Hair Pigmentation

Abstract: Protein oxidative degradation is implicated in a wide range of deleterious effects. For human hair, this oxidative damage can lead to significant observable changes in fiber physical and visual properties. A redox proteomic approach was applied to map molecular modification in human hair proteins and correlate this modification with the abundance of copper (II) ions, the levels of UV exposure and the general level of hair pigmentation. An increase in oxidative modification was observed with increasing copper (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The data strongly suggest that copper ions increase •OH radical photogeneration in hair under wet conditions. This result supports previous studies, which showed that copper ions in hair adsorbed from tap water increased the degree of damage caused by sunlight, in particular by increasing the amount of protein lost from hair during shampooing .…”
Section: Resultssupporting
confidence: 92%
“…The data strongly suggest that copper ions increase •OH radical photogeneration in hair under wet conditions. This result supports previous studies, which showed that copper ions in hair adsorbed from tap water increased the degree of damage caused by sunlight, in particular by increasing the amount of protein lost from hair during shampooing .…”
Section: Resultssupporting
confidence: 92%
“…The loading plots indicated that the elements Cu and S were relevant for this clustering of samples, as well as the scattering of Rh Kα (0.62 Å). The detection of Cu can be also associated to the oxidative alteration in hair treated, which increases the content of ions Cu (II), independent of the hair color …”
Section: Resultsmentioning
confidence: 99%
“…[ ] It is important to note that some breakdown products are photosensitizers [ ] as are the trace metals copper and iron. [ ]…”
Section: Physics: the Hair Phenotype From Macro To Molecular Scalementioning
confidence: 99%